Psychological Empowerment Model in Iranian Pregnant Women - Taghipour, Ali (Int J Community Based Nurs Midwifery, 2016)
BACKGROUND: Women’s empowerment programs during pregnancy focus primarily on increasing women’s health goals and psychological empowerment has been considered important in most issues related to pregnant mothers’ mental health. Using path analysis, this study aims to examine the direct and indirect components of psychological empowerment of pregnant mothers. METHODS: This model-testing study was conducted in Gorgan, northwest of Iran during three months in spring of 2015. Through random cluster sampling, a total number of 160 pregnant women were selected from 10 urban medical centers and clinics as primary centers. We used Spritzer’s Psychological empowerment scale. Suitable sampling based on Nunally and Bernstein was followed in the model. The relationships between the dependent variables were then examined by means of path analysis using Amos 18. RESULTS: The psychological empowerment of pregnant mothers (PEPW) model is impacted by individual factors, such as marriage age and employment, including some subjectively rated factors such as marital satisfaction and experience of violence. The PEPW model was deemed appropriate as optimum conditions indicators of goodness of fit; low index of χ2/df shows little difference between the conceptual model and observed data, while RMSEA value indicated the goodness of fit. Other indicators such as CMIN=0.957, CMIN/DF=0.957, P-CLOSE=0.418, χ2=0.957 and probability level=0.328 the fact that the model is ideal. The mothers’ employment had the highest coefficient in the PEPW path model .731 (0.443, 0.965) bootstrap confidence intervals by 95%, and with a p-value of less than 0.05. CONCLUSIONS: The mothers’ employment is the most important factor in psychological empowerment, but it cannot be addressed quickly. Programming to increase marital satisfaction followed by a decrease in family violence and prevention of early marriage are necessary for promotion of psychological empowerment during pregnancy.